Polyetheretherketone development in bone tissue engineering and orthopedic surgery - Wei, Zhanqi; Zhang, Ze; Zhu, Wei; Weng, Xisheng (Frontiers in Bioengineering and Biotechnology, 2023)
Polyetheretherketone (PEEK) has been widely used in the medical field as an implant material, especially in bone tissue engineering and orthopedic surgery, in recent years. This material exhibits superior stability at high temperatures and is biosecured without harmful reactions. However, the chemical and biological inertness of PEEK still limits its applications. Recently, many approaches have been applied to improve its performance, including the modulation of physical morphology, chemical composition and antimicrobial agents, which advanced the osteointegration as well as antibacterial properties of PEEK materials. Based on the evolution of PEEK biomedical devices, many studies on the use of PEEK implants in spine surgery, joint surgery and trauma repair have been performed in the past few years, in most of which PEEK implants show better outcomes than traditional metal implants. This paper summarizes recent studies on the modification and application of biomedical PEEK materials, which provides further research directions for PEEK implants.